Prolonged survival by combination treatment with a standardized herbal extract from Japanese Kampo-medicine (Juzentaihoto) and gemcitabine in an orthotopic transplantation pancreatic cancer model - Napp, Joanna; Siebel, Paulina; Rausch, Hans; Kuchta, Kenny; Efferth, Thomas; Alves, Frauke; Ellenrieder, Volker; Cameron, Silke (Frontiers in Oncology, 2024)
Pancreatic ductal adenocarcinoma (PDAC) is characterized by its poor prognosis. Traditional Japanese herbal medicine (Kampo), such as Juzentaihoto (a standardized combination of 10 herbal extracts), has shown immune modulatory effects, modulation of microcirculation, and amelioration of fatigue. It is administered to patients to prevent deterioration of cachexia and counteract side effects of chemotherapy. The effect of Juzentaihoto with or without standard chemotherapy (Gemcitabine) on survival and tumor microenvironment was studied in an immunocompetent pancreatic cancer mouse model. Following tumor development ±12 days after orthotopic implantation of murine pancreatic cancer cells (KPC) into the pancreas of C57BL/6 mice, the mice were treated with Gemcitabine, Juzentaihoto, their combination (Gem/Juz) or NaCl (Ctr.). Combination treatment significantly prolonged survival (+38%) of tumor bearing mice, compared to controls as well as Gemcitabine or Juzentaihoto monotherapy. Macrophage (CD68+) infiltration in pancreatic tumors was significantly enhanced in Gem/Juz – treated animals, compared with controls (p < 0,001), with significant increases of both, macrophages (CD68+) and for lymphocytes (CD45+), especially at the tumor front. In vitro, Juz- or Gem/Juz-treated KPC tumor cells secreted significantly more macrophage-chemoattractant cytokines, e.g., CCL2, CCL20, and CXCL2, whilst Juz- and Gem/Juz-treated macrophages (MH-S) secreted cytokines of the M1 phenotype, e.g., IL6, TNF-α, and IL12. It has been shown that tumor cells recruit and polarize macrophages towards tumor-associated macrophages (TAM). Our results indicate a change in macrophage polarization which not only induced anti-tumor immune-cell activity and cytokine release, but also suggests amelioration of Gemcitabine efficacy as DNA-analogue and as partial antitumor antigen. We propose that the increased survival of tumor bearing mice after Gem/Juz combination treatment is due to the restored cytotoxicity of Gemcitabine and changes in the tumor-microenvironment - induced by Juzentaihoto - such as an increased number of M1 macrophages.